EFFEKTIVITAS METODE PEMBELAJARAN THINK-TALK-WRITE TERHADAP HASIL BELAJAR MATA PELAJARAN TEKNIK BUBUT SISWA KELAS XI SMK MUHAMMADIYAH 3 YOGYAKARTA - Endar Subekti; Tarto Sentono (Jurnal Taman Vokasi, 2016)
The objectives of this study are (1) to describe the effectiveness of think-talk-write teaching method toward learning achievement of mechanical machining lathe, (2) to describe the effectiveness of demonstration teaching method toward learning achievement of mechanical machining lathe, and (3) the teaching methods that are more effective between think-talk-write and demonstration among the eleventh grade students of vocational high school Muhammadiyah 3 Yogyakarta. Data collection techniques used observation and test. Hypothesis testing used descriptive analysis and t test that was started by using normality and homogeny test. This study shows that (1) think-talk-write teaching improved learning achievement of mechanical machining lathe among the eleventh grade students of vocational high school Muhammadiyah 3 Yogyakarta with the average score 15.29. (2) Demonstration teaching improved learning achievement of mechanical machining lathe among the eleventh grade students of vocational high school Muhammadiyah 3 Yogyakarta with the average score 13.13. (3) Based on the result of analysis, the score of tobs = 2.152 > ttable = 2.042 with the significant score 0.035 < 0.05, the mean score of learning achievement by usingÂ  think-talk-write teaching method was 15.29, and the mean score of learning achievement by usingÂ  demonstration teaching method was 13.13. Based on those mean scores, it could be concluded that the use of think-talk-write teaching method was higher that demonstration teaching method, it means that of think-talk-write teaching method was more effective that demonstration teaching method.Â